EXPLANATION OF THE VERBS OF THE FIRST CHAPTER IN "TASRIF UL-AF'AL" BY MUHAMMAD IBN ABI ALQASIM AL-MU'AZZI (Archive of Conferences, 2021)
It is well known that one cannot see the future without studying history. An expert in each field refers to the history of the science or profession of his or her specialty. Therefore, in the study of the Arabic language and its grammar, we consider it a matter of urgency to study the works of scholars of grammar and grammar that we know or do not know, and to bring them into scientific circulation